2008
DOI: 10.1098/rspb.2008.0720
|View full text |Cite
|
Sign up to set email alerts
|

Egg colour mimicry in the common cuckooCuculus canorusas revealed by modelling host retinal function

Abstract: Some parasite cuckoo species lay eggs that, to the human eye, appear to mimic the appearance of the eggs of their favourite hosts, which hinders discrimination and removal of their eggs by host species. Hitherto, perception of cuckoo-host egg mimicry has been estimated based on human vision or spectrophotometry, which does not account for what the receivers' eye (i.e. hosts) actually discriminates. Using a discrimination model approach that reproduces host retinal functioning, and museum egg collections collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
122
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 54 publications
(78 reference statements)
3
122
0
Order By: Relevance
“…In the light of recent advances in analyzing color differences as seen by nonhuman animals (6, 7), three studies have used advanced perceptual models of avian discrimination to investigate cuckoo and host egg coloration (8)(9)(10). These confirmed that quantification of visual signals used by hosts to detect parasitism provides much greater insights when analyzed with models of bird vision than does subjective human assessment (5).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In the light of recent advances in analyzing color differences as seen by nonhuman animals (6, 7), three studies have used advanced perceptual models of avian discrimination to investigate cuckoo and host egg coloration (8)(9)(10). These confirmed that quantification of visual signals used by hosts to detect parasitism provides much greater insights when analyzed with models of bird vision than does subjective human assessment (5).…”
mentioning
confidence: 66%
“…These confirmed that quantification of visual signals used by hosts to detect parasitism provides much greater insights when analyzed with models of bird vision than does subjective human assessment (5). However, although valuable, these studies were not directly linked to rejection experiments (8), involved species that were rarely parasitized and artificial eggs that were not a close match to host egg colors (9), or involved systems in which host rejection of foreign eggs does not occur (10).…”
mentioning
confidence: 99%
“…Cuckoo females belong to different genetic races, each of which selectively targets a host species. To sneak their eggs into host nests, many cuckoo host-races have evolved remarkable egg mimicry [11][12][13][14] . Hosts can then defend themselves by evolving better discrimination abilities or by evolving more recognizable egg pattern signatures that facilitate detection of an imposter egg 9,15,16 .…”
mentioning
confidence: 99%
“…Hosts can then defend themselves by evolving better discrimination abilities or by evolving more recognizable egg pattern signatures that facilitate detection of an imposter egg 9,15,16 . Evidence for enhanced discrimination by hosts comes from many studies demonstrating that host discrimination of foreign eggs is at its most refined in species that are parasitized by common cuckoo host-races with nearperfect egg mimicry [11][12][13][14] . However, evidence for the evolution of recognizable egg pattern signatures by common cuckoo hosts is more mixed 7 .…”
mentioning
confidence: 99%
“…It is therefore important to use models of avian vision that account for what the receiver's (i.e. host's) eye actually can perceive as colour matching [52,53]. Here, we ran (Vorobyev -Osorio) physiological models [54] with AVICOL software v. 3 [55] that reproduce host retinal functioning and that account for nest luminosity and bird sensitivity for estimating colour (i.e.…”
Section: (A) Data Collectionmentioning
confidence: 99%